Pediatric Renal Biopsies in India: A Single-Centre Experience of Six Years - Kanodia, Kamal V. (Nephrourol Mon, 2015)
BACKGROUND: Renal biopsy is a well-established diagnostic modality for the assessment of kidney diseases in children. It can provide diagnostic precision and prognostic value and guide in therapeutic options for many renal diseases. OBJECTIVES: This report describes the indication, histopathological patterns, and epidemiology of renal diseases in children in India. PATIENTS AND METHODS: This is a single-center study on renal biopsies performed between January 2008 and December 2013 in 346 children (age ≤ 14 years). RESULTS: Eleven (3.17%) biopsies were inadequate, and 335 biopsies were considered for analysis. The mean age was 7.91 ± 3.04 years with a predominance of males (68.1%). Nephrotic syndrome (46.2%) was the most common indication, followed by urinary abnormality (41.19%), acute nephritic syndrome (10.74%), and chronic renal failure (1.79 %). Primary glomerulonephritis (GN) was predominant (81.79%), and secondary GN constituted 16.12% of the biopsies. Primary GN included mesangial proliferative GN (MePGN), IgM nephropathy, focal segmental glomerulosclerosis, minimal change disease, IgA nephropathy, membranoproliferative GN, membranous nephropathy, crescentic GN, and post-infectious GN. Secondary GN revealed lupus nephritis, hemolytic uremic syndrome, amyloidosis, and hypertensive nephropathy. Tubulointerstitial nephritis was observed in 2.08%. The most common histological pattern of primary GN was MePGN (20%) and in secondary GN it was lupus nephritis (7.76%). CONCLUSIONS: The present study provides data on the epidemiology of renal diseases in children in India and will be helpful for developing a national registry and devising therapeutic guidelines.